2015
DOI: 10.1038/onc.2015.271
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of miR-214-3p in esophageal squamous cancer cells enhances sensitivity to cisplatin by targeting survivin directly and indirectly through CUG-BP1

Abstract: Based on its marked overexpression in multiple malignancies and its roles in promoting cell survival and proliferation, survivin is an attractive candidate for targeted therapy. Towards this end, a detailed understanding of the mechanisms regulating survivin expression in different cancer cells will be critical. We have previously shown that the RNA-binding protein (RBP) CUG-BP1 is overexpressed in esophageal cancer cells and post-transcriptionally regulates survivin in these cells. The objective of this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
100
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(103 citation statements)
references
References 34 publications
3
100
0
Order By: Relevance
“…In the OSCC xenograft model, both tumor development and growth of established tumors was inhibited with survivin-lentivirus therapy. Similar growth inhibitory effects of survivin have been observed by using anti-survivin siRNA in esophageal [87, 130] and skin SCC tumor xenograft models [103].
Fig.
…”
Section: Therapeutic Targeting Of Survivinsupporting
confidence: 77%
“…In the OSCC xenograft model, both tumor development and growth of established tumors was inhibited with survivin-lentivirus therapy. Similar growth inhibitory effects of survivin have been observed by using anti-survivin siRNA in esophageal [87, 130] and skin SCC tumor xenograft models [103].
Fig.
…”
Section: Therapeutic Targeting Of Survivinsupporting
confidence: 77%
“…This seminal investigation recognized the downregulatory effect of miR-484 on cytidine deaminase (CDA), which is a major molecular player in controlling cell proliferation through its suppressive function on cyclin E-CDK2 signalling, thereby inhibiting any cell-cycle progress [59]. Interestingly, the investigation conducted by Phatak and colleagues on oesophageal squamous cancer cell line models revealed that overexpression of miR-214-3p resulted in the sensitization of such tissue cultures to cisplatin [171]. Such a reduction in chemoresistance by miR-214-3p was mediated by direct regulation of surviving expression, together with indirect regulation by means of downregulation of CUG-BP1, leading to decreased mRNA stability in the targeted tumour cells [171].…”
Section: Influences Of Mirnas In Cancer Chemoresistancementioning
confidence: 99%
“…Interestingly, the investigation conducted by Phatak and colleagues on oesophageal squamous cancer cell line models revealed that overexpression of miR-214-3p resulted in the sensitization of such tissue cultures to cisplatin [171]. Such a reduction in chemoresistance by miR-214-3p was mediated by direct regulation of surviving expression, together with indirect regulation by means of downregulation of CUG-BP1, leading to decreased mRNA stability in the targeted tumour cells [171]. …”
Section: Influences Of Mirnas In Cancer Chemoresistancementioning
confidence: 99%
“…Some miRNAs confer drug resistance through regulation of the survivin level [105]. A recent study showed that overexpression of miR-214-3p in esophageal squamous cancer cells enhanced sensitivity to cisplatin by directly targeting survivin [106]. Similarly, miR-542-3p, another tumor-suppressive miRNA, could also directly downregulate the expression of survivin [107,108].…”
Section: Targeting Of Survivin Regulatorsmentioning
confidence: 96%